2022
DOI: 10.3390/ijerph19158924
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Referrals of Children and Adolescents to the Psychiatric Emergency Room Is Evident Only in the Second Year of the COVID-19 Pandemic—Evaluating 9156 Visits from 2010 through 2021 in a Single Psychiatric Emergency Room

Abstract: Introduction: The COVID-19 pandemic affected the wellbeing of children and adolescents. The psychiatric emergency room (ER) is the hub of psychiatric emergencies and reflects clinically significant mental problems. Previous studies compared 2019 and 2020 and observed a decline in ER referrals. The current study focused on the continuous trend of referrals from 2010 to the end of 2021. Method: In our observational retrospective study, we procured data from 9156 child and adolescent referrals to our psychiatric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
(48 reference statements)
2
6
0
Order By: Relevance
“…However, if this had been the case, then a larger proportion of the ER visits would have resulted in hospitalization rather than in discharge. The current findings are in accord with a study that covered most of the psychiatric hospital beds for adolescents in Israel and showed a decline in 2020, probably at least partly related to inpatient services and mental health policies [ 24 ]. In the present study, there was no rise in the proportion of hospitalizations from ER visits; as such, the severity of the emergency seems not to have been the central reason for the decline.in ER referrals during the pandemic.…”
Section: Discussionsupporting
confidence: 91%
“…However, if this had been the case, then a larger proportion of the ER visits would have resulted in hospitalization rather than in discharge. The current findings are in accord with a study that covered most of the psychiatric hospital beds for adolescents in Israel and showed a decline in 2020, probably at least partly related to inpatient services and mental health policies [ 24 ]. In the present study, there was no rise in the proportion of hospitalizations from ER visits; as such, the severity of the emergency seems not to have been the central reason for the decline.in ER referrals during the pandemic.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, there was a decline in children’s and adolescents’ visits to psychiatric ERs during the early stages of the pandemic [ 7 , 8 ]. Conversely, in a recent study we showed that the first year of the COVID-19 pandemic was no different from the continuous decade long rise of referrals to the children and adolescents’ psychiatric ER and the second year showed an additional incline beyond the general trend [ 9 ]. There has been also a rise in visits of patients with severe mental disorders such as psychotic spectrum disorders and bipolar disorder [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that self-rated psychological problems, functional impairment, depression, and referral to psychiatric emergency services, appeared higher among young people after school re-openings ( 15 , 16 ).…”
Section: Discussionmentioning
confidence: 99%